Does democracy reduce the HIV epidemic? Evidence from Kenya - Antoine Marsaudon; Josselin Thuilliez (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
Does democracy help Kenyan citizens to struggle against the HIV epidemic? Yet, very little attention has been devoted to establish whether political regimes react differently to the HIV infection. Using an electoral definition of democracy makes a contribution in understanding which aspects of political rules matter to manage the disease. Using a difference-in-difference design that draws upon pre-existing variations in HIV intensity and cohort's exposure to democracy, we find that a person living under democracy is less likely to have a HIV infection. Further, we present some evidence of ethnic favoritism and gender disparities during periods of non-democracy.
Keywords: I15; I18; O15; O38; P51; 330; institution; democracy; HIV; Health; Kenya